Frozen Elephant Trunk: A technique which can be offered in complex pathology to fix the whole aorta in one setting - Kratimenos Theodoros; Ashrafian Hutan; Anagnostakou Vania; Kokotsakis John; Athanasiou Thanos (Journal of Cardiothoracic Surgery, 2011)
Abstract We report a case of treating complex aortic pathology with the use of the Frozen Elephant Trunk technique in a patient with chronic type B aortic dissecting aneurysm associated with arch and ascending aorta dilatation, proximal aortic disease and coronary disease. The case was further complicated due to the involvement of the abdominal vessels and preexisting femoral to femoral crossover bypass. In addition the patient had a tracheostomy for laryngeal cancer. We emphasize the role of the Frozen Elephant Trunk to fix the whole aorta in one setting with special attention given to the changes taking place in vascular perfusion following correction and reconstitution of the true lumen.